Endovascular repair of direct carotid–cavernous fistula in Ehlers–Danlos type IV. (8th January 2014) - Linfante, Italo; Lin, Eugene; Knott, Eric; Katzen, Barry; Dabus, Guilherme
Abstract : Ehlers–Danlos syndrome (EDS) type IV is a collagen vascular disease with an autosomal dominant inheritance caused by COL3A1 mutation. Patients with EDS type IV can present with organ rupture, spontaneous arterial dissections and ruptured aneurysms. Because of their propensity to form arterial dissections, aneurysms and rupture, they can develop carotid–cavernous fistula (CCF) after minor trauma or spontaneously. In EDS, it has been reported that even conventional catheter diagnostic angiography may result in large artery dissections and vessel rupture. In addition, the treatment of CCF in EDS type IV can result in up to 59% mortality after initial treatment, of which 23% is attributed to direct complications of treatment. We present the case of a patient with EDS type IV who previously had spontaneous dissection and multiple pseudoaneurysms of both the iliac and femoral arteries and the distal abdominal aorta. Several years later the patient developed a direct type A CCF which was successfully treated with endovascular embolization using a transvenous approach with detachable coils. The literature pertaining to CCF in EDS type IV and its treatment is reviewed.